Meningkatkan Kemampuan Basic Grammar (Personal Pronoun) Menggunakan Metode menciptakan Lirik Lagu - Alawiyah, Rosidah; Suktiningsih, Wiya; Alfilail, Nur; Farwati, Wiwik Wida; Saputra, Sahdan (CV. Global Cendekia Inti, 2024)
This study aims to enhance English grammar learning among high school students by utilizing songs as an educational tool. The study addresses the issues of low motivation and the challenges students face in learning English grammar, often attributed to monotonous and non-contextual teaching methods. Conducted at SMAN 1 Gerung, West Lombok Regency, this community service activity involved a team of lecturers from Bumigora University. The methodology comprised planning, implementation, and evaluation phases. During the implementation stage, learning materials were presented using PowerPoint, followed by creating song lyrics from the studied sentences. Evaluations revealed improved student understanding of basic grammar, a more enjoyable learning environment, and increased motivation. These findings suggest that incorporating songs into grammar instruction can enhance learning effectiveness and boost student motivation.